Spread through air spaces (STAS): a comprehensive update - Warth, Arne (Translational Lung Cancer Research, 2017)
The new concept of spread through air spaces (STAS) was introduced for pulmonary adenocarcinomas (ADC) in the 2015 World Health Organization (WHO) classification for lung cancer. Yet available data demonstrate that STAS is of high prognostic impact and associated with specific clinic-pathological characteristics. This article provides a comprehensive overview on recent developments in this field.